Experiential Learning Improves Writing Skills and Creative Thinking: Pembelajaran Berbasis Pengalaman Meningkatkan Keterampilan Menulis dan Berpikir Kreatif - Hikmah, Nur; Sulfasyah, Sulfasyah; Arif, Tarman A. (Indonesian Journal of Innovation Studies, 2025)
General Background: In the era of competency-based education, fostering both writing and creative thinking skills is crucial for elementary students. Specific Background: However, students in remote areas often face challenges in developing these abilities due to limited learning models and contextual support. Knowledge Gap: Prior studies have rarely explored the integrated effects of experiential learning on both writing performance and creative cognition in under-resourced schools. Aims: This study aims to examine the impact of the experiential learning model on students' travel report text writing skills and creative thinking abilities.Results: Using a quantitative method with a non-equivalent control group design, the study involved 47 fourth-grade students at SD Negeri Terpencil 350 Kahaya. Data analysis using t-tests and one-way MANOVA revealed that the experiential learning model significantly improved both writing skills (Sig. = 0.20 < α = 0.25) and creative thinking skills (Sig. = 0.21 < α = 0.25), with a combined multivariate effect (p = 0.202). Novelty: This research highlights the dual effectiveness of experiential learning in enhancing literacy and higher-order thinking simultaneously. Implications: The findings suggest that implementing experiential learning in remote schools can bridge educational disparities by cultivating critical 21st-century competencies. Highlights: Demonstrates experiential learning's dual impact on writing and creativity. Highlights educational challenges in remote school settings. Provides evidence through MANOVA and t-test statistical analysis. Keywords: Experiential Learning Model, Travel Report Writing, Creative Thinking, Elementary Education, Remote Schools